EXPERIMENT AS A METHOD FOR ASSESSMENT OF EFFICIENCY OF PRACTICES AND INNOVATIONS IN THE FIELD OF HIGHER EDUCATION - Natalia G. Maloshonok; Inna F. Devyatko (Высшее образование в России)
The article presents fundamental propositions for conducting experimental study in the field of education in order to assess efficiency of educational practices and innovations. Experiment is considered as a method that has advantages in exploring casual link between independent and dependent variables. In addition, the article contains the description of threats to validity and the demonstration of concrete examples and their critique.